Very Large Scale PV Power Generation for Shifting to a Renewable Energy Future - Namjil , Enebish; Keiichi , Komoto; Christian , Breyer; Sicheng , Wang; Edwin, Cunow; David , Faiman; Parikhit , Sinha; Tomoki , Ehara (Scientific transaction of the National University of Mongolia. Physics, 2022)
In order to meet the environmental challenge in the 21st Century, renewable energy must play an important role. PV is one of the most promising renewable energy technologies. It may be no exaggeration to say that we’re now coming to the stage of energy transition by PV power plants. PV power plants came on the market first in the latter half of 2000s. Since then, a capacity of the largest PV power plant in the world has been broken every year. In 2014, some PV plants over 500MW started operation. Currently, a share of PV power plants will be 15% or more of the total PV installation in the world. The technical and economic feasibility of the large scale PV power plants are already proven, and the environmental and socio-economic benefits can make the project more attractive. To deploy large scale PV power plants as a major power source, the feasibility and expected benefits of PV power plants are analysed, as well as a potential for global energy system.